IBM DS8880 integrated copy services manager and LDAP Client on the HMC - Dufrasne, Bertrand; Iyabi, Jean (IBM redpaper., 2017)
IBM® Copy Services Manager (CSM) is a replication management solution that is based on the IBM Tivoli® Productivity Center for Replication technology. CSM inherits all the Tivoli Productivity Center for Replication capabilities and continues to provide Copy Services solutions for most IBM storage offerings. The IBM DS8880, starting with firmware Release 8.1, Licensed Machine Code (LMC) 8.8.10.xx.xx, includes CSM for the IBM System Storage® DS8000®, which is pre-installed on the Hardware Management Console (HMC). If you ordered the CSM feature code as part of your IBM DS8000 system configuration, you only need to activate CSM. CSM as installed on the HMC, or acquired separately, includes a lightweight build of the IBM WebSphere® Liberty server code, to use to authenticate CSM users through a Lightweight Directory Access Protocol (LDAP). The same integrated LDAP support can be used for remote authentication of DS8000 users. Furthermore, if you simply want to take advantage of the CSM LDAP client for DS8000 LDAP authentication, the CSM license and CSM activation are not required. This IBM Redpaper"!publication describes the requirements for setup and usage of CSM on the DS8000 HMC, for both Copy Services management and LDAP authentication